Contribution of Land Use Change and Land Cover to Climate Change Coastal Areas and Their Impacts: Evidence in Jayapura City, Papua Province, Indonesia - Pamungkas, Guntur Bagus; Andriani, Vida (Department of Urban and Regional Planning, Diponegoro University, 2023)
This study aims to analyze land use and land cover change (LULCC) that affects climate change, especially in the coastal areas of Jayapura City as well as disaster mitigation strategies for vulnerabilities caused in the future. The method used is descriptive quantitative by identifying land use change with the spatio-temporal remote sensing method using the gaussian mixture model in the dzetsaka plugin in QGIS 3.22.4 software and strategies for handling climate change vulnerabilities in the coastal areas of Jayapura City. The geospatial process is carried out for socio-environmental aspects that apply that in the Jayapura city area experienced a significant decrease in vegetation ranging from 67.28% or an area of 29,875,904 ha. This shows the category as a deforestation area that is prone to the impacts of coastal climate change in Jayapura City. In such vulnerabilities it is necessary to take preventive measures such as reforestation or even greening that serve for proper and continuous monitoring. As in this coastal area, it is hoped that it will always have a maintained ecosystem balance to realize local environmental sustainability in the future.